Empirical Evidence of Forensic Auditing and Whistleblower on Fraud Control, Organizational Performance; A Case Study of Public and Private Sectors of Pakistan - Waqar Dilshad; Muhammad Irfan; Syed Muhammad Kamran Javed; Zeenat Aftab (Journal of Accounting and Finance in Emerging Economies, 2020)
Aim of the Study: Fraud proceeds to be a genuine obstacle to the survival and fruitful operations in business organizations hence requiring that they create vigorous measures to as much as conceivable diminish the event. The over required the require for this think about which examined the relationship between forensic and the whistle blowing of fraud control and organization performance within the public and private sector in Pakistan. Forensic reviewing may be a quickly developing field of bookkeeping that includes an investigative fashion of bookkeeping utilized to disclose the exercises of people or the corporate sector. Pakistan public and private sectors are more vulnerable to fraud these days. This article evaluates the relationship between forensic audit or whistle blowing on fraud control and organization performance in the public or private sector and assessed the most effective relationship between whistle blowing and forensic auditing as it regards fraud unearthing. Research Methodology: The research will embrace the deductive approach under positivism paradigm. The study adopted a survey design of research in cross-section.Data Analysis:For data collection, 230 questionnaires distributed to financial public and private sectors and 211 questionnaires were got completed. Females were 24 of 211 (f=11.4%) and males were 187 of 211 (f= 88.6%) . data were analyzed using Correlation and regression techniques by SPSS 20. The findings forensic audit and whistle blowing has a positive relationship with fraud control and organization performance.Conclusion and Recommendation:The study was conducted in Multan, Pakistan due to time and cost constraints. The forensic audit should be included in the statutory audit. Forensic auditors should be included in during audit in the audit team. Professional accounting bodies in Pakistan should train their members to become forensic auditors. Forensic auditing should be made a field of specialization in our higher institution especially in the postgraduate school and business institutions.